AFASIA PRAGMÁTICA: CÉREBRO, LINGUAGEM E COMUNICAÇÃO (Muitas Vozes, 2022)
This article describes the linguistic behavior of individuals diagnosed with mild Frontal Lobe Syndrome or Pragmatic Aphasia, a neurological condition resulting from brain damage that affects linguistic areas and the semantic processes of understanding. Resorting to the pragmatic conception of language, in the analysis of the linguistic traits that characterize the pathology of brain-injured subjects who present alterations and contextual communicative difficulties. The theoretical framework for the analysis is composed of the functional model of the brain, which allows the classification of aphasia from a linguistic point of view and, to address the pragmatic and cognitive aspects of the Frontal Lobe Syndrome, the relationships between communication and context are used in the Relevance Theory (SPERBER; WILSON, 2001).